A model of the U.S. balance of payments - Kenen, Peter B.; Dungan, D. Peter; Warner, Dennis L. (Lexington, Mass.: Lexington Books, 1978)
This book presents a detailed model of the U.S balance of payments. The model is estimated from quarterly data spanning 1960 to 1973, using simple statistical techniques, and is linked to a medium sized model of the U.S economy. It was designed to study the effects on the balance of payments of changes in fiscal and monetary policies, exchange rates, and capital controls.
Includes index.
Includes bibliographical references
usc 24/08/18
Loans
Keywords: Balance of payments; United States